2010
DOI: 10.1128/aem.01624-09
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Bacillus pumilus Strain Highly Active against Ceratitis capitata (Wiedemann) Larvae

Abstract: Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), the Mediterranean fruit fly (medfly), is one of the most important fruit pests worldwide. The medfly is a polyphagous species that causes losses in many crops, which leads to huge economic losses. Entomopathogenic bacteria belonging to the genus Bacillus have been proven to be safe, environmentally friendly, and cost-effective tools to control pest populations. As no control method for C. capitata based on these bacteria has been developed, isolation of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 71 publications
0
33
0
1
Order By: Relevance
“…Bacillus pumilus is a naturally occurring bacterium that is especially common in soil and on dead plant tissue (Priest 1993). Molina et al (2010) also showed that this bacterium is toxic to Ceratitis capitata larvae (Weidemann) (Diptera: Tephritidae). With this study, we also showed that the genus of Bacillus might be associated with stored product pests in different ways, pathogenic or symbiotic.…”
Section: Discussionmentioning
confidence: 94%
“…Bacillus pumilus is a naturally occurring bacterium that is especially common in soil and on dead plant tissue (Priest 1993). Molina et al (2010) also showed that this bacterium is toxic to Ceratitis capitata larvae (Weidemann) (Diptera: Tephritidae). With this study, we also showed that the genus of Bacillus might be associated with stored product pests in different ways, pathogenic or symbiotic.…”
Section: Discussionmentioning
confidence: 94%
“…The first study that demonstrated the entomopathogenicity of B. pumilus is detailed in a patent that describes a strain active against the corn rootworm (e.g., Diabrotica undecimpunctata (Mannerheim, 1843), Diabotrica longicornis (Say, 1824)), the armyworm (Spodoptera exigua (Hubner, 1808)), and some species of nematodes (Heins et al 1999). The entomopathogenic activity of B. pumilus was confirmed in a study that described the isolation of the strain 15.1, a highly toxic strain against Mediterranean fruit fly larvae, Ceratitis capitata (Wiedemann, 1824) (Molina et al 2010). Since B. pumilus has never been considered as a classic entomopathogenic bacteria, the origin and the possible evolutionary route of the insecticidal activity of the B. pumilus 15.1 strain is a fairly interesting topic that would help to explain the process of pathogenicity.…”
Section: The Sociability Of Entomopathogenic Bacteria and Its Ecologymentioning
confidence: 84%
“…In addition, the presence of crystals has been described in sporulating cultures of B. pumilus 15.1 that are similar to the Cry proteins of B. thuringiensis (Molina et al 2009). The role of these structures has not yet been elucidated.…”
Section: The Sociability Of Entomopathogenic Bacteria and Its Ecologymentioning
confidence: 99%
See 2 more Smart Citations